Immune tolerance induction in hemophilia. (March 2015) - Mancuso, Maria Elisa; Cannavò, Antonino
The development of inhibitors is the main complication of hemophilia therapy. Inhibitors occur in 25–30% and in 2–5% of patients with severe hemophilia A and B, respectively. They render treatment and prevention of bleeds difficult. The only known therapeutic strategy able to eliminate inhibitors is immune tolerance induction (ITI) that consists in regular high-dose FVIII/FIX infusions. ITI is a demanding treatment both for patients/parents and clinicians, it is costly, but provides 60–80% chance of success. Although used since late 1970, many aspects of ITI still needs to be optimized and further investigated. This review is aimed at reporting what is known from the published literature and what still need to be investigated in this field.